1999
DOI: 10.1016/s0022-5347(05)68171-2
|View full text |Cite
|
Sign up to set email alerts
|

Von Recklinghausen′s Disease and Pheochromocytomas

Abstract: Pheochromocytomas occur in a small but defined number of patients with von Recklinghausen's disease, and can be associated with significant morbidity and mortality if not detected. Screening of patients with von Recklinghausen's disease and hypertension or before provocative procedures or pregnancy seems to be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
175
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(185 citation statements)
references
References 78 publications
6
175
0
4
Order By: Relevance
“…This may be, at least partly, explained by the lack of symptoms (84% of asymptomatic PHEO) and the non-secreting nature of a large part of detected PHEO (50%), already described in 2013 by Haissaguerre et al (11) in a retrospective study performed in sporadic PHEO. In the literature, the age at onset of PHEO is typically the fourth decade of life, both in NF1-associated and sporadic cases (12,13), without influence of gender. In our study, age at diagnosis is a little bit higher, at 55.3 ± 13.7 years, for secreting PHEO and 53.2 ± 15.9 years for non-secreting PHEO, without significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be, at least partly, explained by the lack of symptoms (84% of asymptomatic PHEO) and the non-secreting nature of a large part of detected PHEO (50%), already described in 2013 by Haissaguerre et al (11) in a retrospective study performed in sporadic PHEO. In the literature, the age at onset of PHEO is typically the fourth decade of life, both in NF1-associated and sporadic cases (12,13), without influence of gender. In our study, age at diagnosis is a little bit higher, at 55.3 ± 13.7 years, for secreting PHEO and 53.2 ± 15.9 years for non-secreting PHEO, without significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Discordant results have been reported on the prevalence of malignant PHEO in NF1. In large series, the metastatic potential of PHEO was estimated to be around 10% (12,14). By contrast, Zinnamosca et al in 2011 (9) found no malignant PHEO in a small series of 48 patients.…”
Section: :4mentioning
confidence: 94%
See 1 more Smart Citation
“…It has been usually described in adult NF1 patients. This percentage rises up to 20-50% among hypertensive NF1 subjects compared to 0.1% of all hypertensive patients [50]. Biochemical screening to exclude or confirm PHEO is recommended in patients with NF1 in case of development of hypertension or other suggestive symptoms [50,51].…”
Section: Pheochromocytomamentioning
confidence: 99%
“…This percentage rises up to 20-50% among hypertensive NF1 subjects compared to 0.1% of all hypertensive patients [50]. Biochemical screening to exclude or confirm PHEO is recommended in patients with NF1 in case of development of hypertension or other suggestive symptoms [50,51]. Symptoms and signs of PHEO result from release of catecholamines and include the classical ‘three H' of hypertension, headaches and hyperhidrosis as well as palpitations and weight loss [52].…”
Section: Pheochromocytomamentioning
confidence: 99%